2017
DOI: 10.1016/j.jphs.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

High salt loading induces urinary storage dysfunction via upregulation of epithelial sodium channel alpha in the bladder epithelium in Dahl salt-sensitive rats

Abstract: We aimed to investigate whether high salt intake affects bladder function via epithelial sodium channel (ENaC) by using Dahl salt-resistant (DR) and salt-sensitive (DS) rats. Bladder weight of DR + high-salt diet (HS, 8% NaCl) and DS + HS groups were significantly higher than those of DR + normal-salt diet (NS, 0.3% NaCl) and DS + NS groups after one week treatment. We thereafter used only DR + HS and DS + HS group. Systolic and diastolic blood pressures were significantly higher in DS + HS group than in DR + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…In short, oxidative stress altered the physiological function of the urothelium and increased bladder sensitivity or sense of urgency in in vivo and in vitro studies, and salt intake was associated with the excessive production of oxidative stress . On the other hand, basic research reported that high salt loading induces urinary storage dysfunction via the upregulation of epithelial sodium channel alpha in the bladder epithelium in Dahl salt‐sensitive rats . Thus, we believe that urgency and urinary incontinence by excessive salt intake are regulated by complex mechanisms.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In short, oxidative stress altered the physiological function of the urothelium and increased bladder sensitivity or sense of urgency in in vivo and in vitro studies, and salt intake was associated with the excessive production of oxidative stress . On the other hand, basic research reported that high salt loading induces urinary storage dysfunction via the upregulation of epithelial sodium channel alpha in the bladder epithelium in Dahl salt‐sensitive rats . Thus, we believe that urgency and urinary incontinence by excessive salt intake are regulated by complex mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…29 On the other hand, basic research reported that high salt loading induces urinary storage dysfunction via the upregulation of epithelial sodium channel alpha in the bladder epithelium in Dahl salt-sensitive rats. 30 Thus, we believe that urgency and urinary incontinence by excessive salt intake are regulated by complex mechanisms. There were some limitations in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between high salt intake and urinary storage symptoms has been evaluated in a few studies. We previously reported that one week of high salt intake in DS rats was associated with upregulated expression of epithelial sodium channel alpha in the bladder epithelium and influenced urinary frequency [12]. Kurokawa et al reported that twelve weeks of high salt intake in DS rats caused urinary storage dysfunction via increased release of ATP and prostaglandin E2 from distended bladder epithelium [13].…”
Section: Discussionmentioning
confidence: 99%
“…Dahl salt-sensitive (DS) and Dahl salt-resistant (DR) rats are widely used for basic studies on the relationship between salt intake and disease [14]. We previously reported that one week of high salt intake in DS rats was associated with the upregulation of epithelial sodium channel alpha expression and contributed to urinary frequency [12]. These results suggest that high salt intake in DS rats induces urinary storage symptoms after short-term exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation